Scott LaFaro - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Red Nichols - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Ray(mond) Brown - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Kid Ory - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Jimmy Blanton - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Doc Cheatham - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Using Visual Mapping to Promote Higher-Level Thinking in Music-Making - Groffman, Joshua; Wolfe, Zora M. (Music Educators Journal, 2019)
What tools are available to foster independent and critical thought in the music classroom? We propose that visual mapping—a method of representing relationships and associations between a main concept and other ideas, subtopics, or examples—is an ideal tool for doing exactly this. After examining the principles and usefulness of mapping in a variety of contexts, we discuss several specific ways in which mapping might be implemented in teaching music. We argue that the central strength of mapping is its ability to encourage users to be explicit and metacognitive about their knowledge. As such, it can be part of a constructivist stance whereby the instructor creates a student-centered classroom in which learners are active, engaged participants in their education.
Keywords: dept.mus; peer-reviewed

Translation of Gottfried Taubert's Rechtschaffener Tantzmeister. - Russell, Tilden A. (2006)
Keywords: dept.mus; faculty_collection; sabbatical_report

Theory and Practice in Eighteenth-Century Dance: The German-French Connection - Russell, Tilden A. (University of Delaware Press ; The Rowman & Littlefield Publishing Group, Inc., 2018)
Theory and Practice in Eighteenth-Century Dance: The German-French Connection is about the intersection of two evolving dance-historical realms-theory and practice-during the first two decades of the eighteenth century. France was the source of works on notation, choreography, and repertoire that dominated European dance practice until the 1780s. While these French inventions were welcomed and used in Germany, German dance writers responded by producing an important body of work on dance theory. This book examines consequences in Germany of this asymmetrical confrontation of dance perspectives. Between 1703 and 1717 in Germany, a coherent theory of dance was postulated that called itself dance theory, comprehended why it is a theory, and clearly, rationally, distinguished itself from practice. This flowering of dance-theoretical writing was contemporaneous with the appearance of Beauchamps-Feuillet notation in the Chorégraphie of Raoul Auger Feuillet (Paris, 1700, 1701). Beauchamps-Feuillet notation was the ideal written representation of the dance style known as la belle danse and practiced in both the ballroom and the theater. Its publication enabled the spread of belle danse to the French provinces and internationally, and encouraged the publication, in different languages, of new dance treatises as well as practical works (manuals, choreographies, recueils) on how to make steps and dance current dances. The Rechtschaffener Tantzmeister, by Gottfried Taubert (Leipzig, 1717), includes a translated edition of Feuillet's Chorégraphie. In the present book, chapters 1, 2, and 5 have to do with how Taubert and his contemporary German authors of dance treatises (Samuel Rudolph Behr, Johann Pasch, Louis Bonin) became familiar with Beauchamps-Feuillet notation and acknowledged the Chorégraphie in their own work, and how Taubert's translation of the Chorégraphie spread its influence northward and eastward in Europe. Chapters 3 and 4 examine the personal and literary interrelationships between the German writers on dance between 1703 and 1717. Chapter 6 examines these writers' invention of a theoria of dance as a counterbalance to dance praxis, compares their dance-theoretical ideas with those of John Weaver in England, and assimilates them all in a cohesive and inclusive description of dance theory in Europe by 1721. Book jacket.
Keywords: 18th century; 18th century; Choreography; 18th century; Dance; 18th century; Dance notation; France; Germany; History; Philosophy; Taubert; Gottfried; active 1717; Dance; dept.mus

The compleat dancing master: a translation of Gottfried Taubert's Rechtschaffener Tantzmeister (1717) - Taubert, Gottfried (Peter Lang, 2012)
Keywords: Dance; Early works to 1800; dept.mus; faculty_collection

The Menuet De La Cour - Russell, Tilden A. (Olms, 2007)
Keywords: History and criticism; History and criticism; Minuets; Minuet (Dance); dept.mus; faculty_collection

Singing with the angels: Foundation documents as evidence for musical life in monasteries of the Byzantine empire - Dubowchik, R. (2002)
Journal Abbreviation: Dumbarton Oaks Pap. Pages: 296 Publication Title: Dumbarton Oaks Pap.
Keywords: dept.mus

To fight the losing war, to remember the lost war: The changing role of Gunka, Japanese war songs - Oba, J. (Global goes Local: Popular Culture in Asia, 2007)
Journal Abbreviation: Global goes Local: Popular Culture in Asia
Keywords: dept.mus

In defense of vom "affect" zur "action" - Russell, T. (Dance Chronicle, 2008)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mus

Modernism in South Asian art music - Scott, S. (The Modernist World, 2015)
Journal Abbreviation: The Modern. World
Keywords: dept.mus

Hearing, Describing, and Creating Melodies in the DAW - Groffman, Josh (POGIL Activity Clearinghouse, 2021)
This activity introduces students to hearing, describing, and creating Melodies in the DAW as part of a general education, lower-level college course. Students with familiarity with concepts of rhythm and meter, the transport controls and basic functionality of the DAW, the piano roll, and entering MIDI notes into the sequencer will, by the end of the activity, be able to define melody and step/leap; describe different melodies and contrast them in terms of contour and rhythm; describe different melodies and contrast them in terms of the variable experience each creates for the listener; and create a basic melody using the piano roll in the DAW. They will continue to develop their critical aesthetic thinking skills (evaluating what makes for variable aesthetic experience in music), as well as oral/written aesthetic communication skills. (communicating their hearing and affective experience of music). Level:UndergraduateSetting: ClassroomActivity Type: Learning CycleDiscipline: MusicCourse: Introduction to Music TechnologyKeywords: Melody, rhythm, meter, contour, DAW, aesthetic
Number: 3
Keywords: dept.mus; peer-reviewed; ⛔ No DOI found